2007
DOI: 10.1016/j.virol.2007.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for resistance of herpes simplex virus type 1 mutants to the sulfated oligosaccharide inhibitor PI-88

Abstract: Herpes simplex virus type 1 variants selected by virus propagation in cultured cells in the presence of the sulfated oligosaccharide PI-88 were analyzed. Many of these variants were substantially resistant to the presence of PI-88 during their initial infection of cells and/or their cell-to-cell spread. Nucleotide sequence analysis revealed that the deletion of amino acids 33-116 of gC but not lack of gC expression provided the virus with selective advantage to infect cells in the presence of PI-88. Purified g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…We have recently found that serial passages of HSV-1 in cultured cells in the presence of the GAG-mimetic oligosaccharide PI-88 (also known as muparfostat) resulted in the selection of viral variants that were resistant to this inhibitor, due to deletion of an entire mucin-like domain located at the N-terminal part of the viral attachment protein gC (12). Interestingly, similar selection experiments performed with HSV-2 resulted in viral variants lacking gG, a virus envelope protein also carrying a mucin-like region (13).…”
mentioning
confidence: 99%
“…We have recently found that serial passages of HSV-1 in cultured cells in the presence of the GAG-mimetic oligosaccharide PI-88 (also known as muparfostat) resulted in the selection of viral variants that were resistant to this inhibitor, due to deletion of an entire mucin-like domain located at the N-terminal part of the viral attachment protein gC (12). Interestingly, similar selection experiments performed with HSV-2 resulted in viral variants lacking gG, a virus envelope protein also carrying a mucin-like region (13).…”
mentioning
confidence: 99%
“…First, intact O-linked glycosylation of glycoprotein mucin domains promote infectivity of human viruses using cell surface glycosaminoglycans as receptors (13). Second, the mucin domains may harbor virus-induced carbohydrate epitopes that may function as selectin ligands (8,12).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular size of the O-linked glycans of the gC-1 mucin domain may vary from monosaccharides to sialylated tetrasaccharides (7,10,11) but possibly also larger structures (8,12). In vitro studies using HSV-1 mutants expressing gC-1 that lack its mucin domain indicated that this domain is involved not only in viral binding to its target cell but also in cell-to-cell spread of virus, which is affected by the number of O-linked glycans in this domain (13,14). Moreover, the mucin domain of gC-1 appears to be involved in expression of virus-induced selectin ligands, a phenomenon of possible relevance for viraemic spread of HSV-1 (8,12,15,16).…”
mentioning
confidence: 99%
“…Therefore, this region of mgG resembles a mucin-like structure. Interestingly, variants of HSV-1 resistant to PI-88 in their initial infection of cells all carried a large deletion of a mucin-like region at the amino-terminal part of the viral attachment protein gC (7). This region of HSV-1 gC was reported to promote attachment of the virus to cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…One approach to further explore the interaction of HSV with HS chains has been the analysis of HSV-1 mutants resistant to sulfated oligo-and polysaccharides, such as heparin (12,29) and carrageenan (4). Furthermore, our recent analysis of HSV-1 variants resistant to the sulfated oligosaccharide PI-88 revealed that this compound specifically targets the mucin-like region at the amino-terminal portion of viral gC (7). Because no similar studies were performed with HSV-2, in the present work we analyzed PI-88-resistant variants of this virus.…”
mentioning
confidence: 99%